1987
DOI: 10.1002/bdd.2510080109
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of drug distribution in vivo on the basis of in vitro binding data

Abstract: For 11 drugs it was investigated whether tissue distribution in vivo can be predicted by use of binding data obtained in vitro. The selection of drugs represented a broad spectrum of physicochemical and pharmacokinetic properties thought to be important for distribution of drugs in vivo. The extent of binding to plasma and to tissue-homogenates of rabbits was determined in vitro. The drug concentrations in plasma, liver, lungs, kidneys, and skeletal muscle of rabbits were determined in vivo after i.v. administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…The central role of pH partitioning in drug distribution, which has been demonstrated in this study in vitro, can be expected to translate to the in vivo situation. Early studies supporting this view showed that the in vivo tissue partition coefficients of various organs cannot be predicted for basic drugs using data from tissue homogenates (Harashima et al, 1984;Schuhmann et al, 1987).…”
Section: Comparison Of Brain Slice and Brain Homogenate Methodsmentioning
confidence: 99%
“…The central role of pH partitioning in drug distribution, which has been demonstrated in this study in vitro, can be expected to translate to the in vivo situation. Early studies supporting this view showed that the in vivo tissue partition coefficients of various organs cannot be predicted for basic drugs using data from tissue homogenates (Harashima et al, 1984;Schuhmann et al, 1987).…”
Section: Comparison Of Brain Slice and Brain Homogenate Methodsmentioning
confidence: 99%
“…More recently, an approach to estimate brain penetration of drugs using binding experiments conducted with homogenates of brain tissue has been described previously (Kalvass et al, 2007). Furthermore, historically, some comparative studies have been conducted on the properties of drug binding to tissues (Kurz and Fichtl, 1983;Schuhmann et al, 1987;Clausen and Bickel, 1993;Ballard et al, 2003). However, a study on the ability to use in vitro tissue-binding experiments to quantitatively predict the V ss of a wide range of drugs has not been conducted.…”
mentioning
confidence: 99%
“…Following this expectation, attempts have been made to predict tissue partitioning from in vitro estimates of unbound plasma fraction and unbound tissue fraction with mixed success (Bickel and Gerny, 1980;Bickel et al, 1987;Schuhmann et al, 1987;Clausen and Bickel, 1993). Previous reports suggest that the dilution, homogenization, and incubation process necessary to determine unbound tissue fraction by equilibrium dialysis may disrupt or destroy intracellular components that contribute to distribution in vivo.…”
mentioning
confidence: 99%